Exploratory Visualization Involving Incremental, Approximate Database Queries and Uncertainty - Fisher, Danyel; Drucker, Steven; König, Arnd Christian (IEEE, 2012)
Large datasets can mean slow queries, for which users must wait. Incremental visualization systems can give faster results at a cost of accuracy. This article asked analysts to use one and report on their results. Their feedback provides suggestions for alternative visualizations to represent a query still in progress.
IEEE Computer Graphics and Applications